The first magnetotelluric image of the lithospheric-scale geological architecture in central Svalbard, Arctic Norway - Thomas I. Beka (Polar Research, 2015)
Magnetotelluric data, collected from 30 stations on Spitsbergen as part of a reconnaissance geothermal resource assessment along a profile with 0.5–3-km spacing in 0.003–1000-s period range, were used to develop a lithospheric-scale two-dimensional (2D) resistivity model, heretofore unavailable for the region. Inverting the determinant of the impedance tensor in 2D, we found the smoothest model fitting the data within a specified tolerance level. We justified the model by perturbing it, performing sensitivity analysis and re-running the inversion with a different algorithm and starting models. From our final model, we constructed a crustal-scale stratigraphic framework, using it to estimate the depth of major geological features and to locate structural deformations. The 2D resistivity model indicates a shallow low resistive (<100 Ωm) Paleozoic–Mesozoic sedimentary sequence, varying laterally in thickness (2–4 km), obstructed by a gently dipping Permian–Carboniferous succession (>1000 Ωm) east of the Billefjorden Fault Zone. Underneath, a (possibly Devonian) basin is imaged as a thick conductive anomaly stretching >15 km downwards. Beneath a deformed Paleozoic–Mesozoic successions, an uplifted pre-Devonian shallow basement (>3000 Ωm) is revealed. We estimated a thin lithosphere, in the range of ca. 55–100 km thick, that could explain the area's elevated surface heat flow (ca. 60–90 mW/m2), consistent with the calculated depth of thermal lithosphere heat-base boundaries for a partially melting mantle. The model indicates a possible replenishment pathway of upward heat transport from the shallow convective mantle to the composite crustal conductive units. This is encouraging for low-enthalpy geothermal development.